Microbial Community Drivers in Anaerobic Granulation at High Salinity - Gagliano, Maria Cristina; Sudmalis, Dainis; Pei, Ruizhe; Temmink, Hardy; Plugge, Caroline M. (Frontiers in Microbiology, 2020)
In the recent years anaerobic sludge granulation at elevated salinities in upflow anaerobic sludge blanket (UASB) reactors has been investigated in few engineering based studies, never addressing the microbial community structural role in driving aggregation and keeping granules stability. In this study, the combination of different techniques was applied in order to follow the microbial community members and their structural dynamics in granules formed at low (5 g/L Na+) and high (20 g/L Na+) salinity conditions. Experiments were carried out in four UASB reactors fed with synthetic wastewater, using two experimental set-ups. By applying 16S rRNA gene analysis, the comparison of granules grown at low and high salinity showed that acetotrophic Methanosaeta harundinacea was the dominant methanogen at both salinities, while the dominant bacteria changed. At 5 g/L Na+, cocci chains of Streptoccoccus were developing, while at 20 g/L Na+ members of the family Defluviitaleaceae formed long filaments. By means of Fluorescence in Situ Hybridization (FISH) and Scanning Electron Microscopy (SEM), it was shown that aggregation of Methanosaeta in compact clusters and the formation of filaments of Streptoccoccus and Defluviitaleaceae during the digestion time were the main drivers for the granulation at low and high salinity. Interestingly, when the complex protein substrate (tryptone) in the synthetic wastewater was substituted with single amino acids (proline, leucine and glutamic acid), granules at high salinity (20 g/L Na+) were not formed. This corresponded to a decrease of Methanosaeta relative abundance and a lack of compact clustering, together with disappearance of Defluviitaleaceae and consequent absence of bacterial filaments within the dispersed biomass. In these conditions, a biofilm was growing on the glass wall of the reactor instead, highlighting that a complex protein substrate such as tryptone can contribute to granules formation at elevated salinity.